TRANSFORMATION OF THE UNIVERSITY hopeful futures for higher education. - Bengtsen, Søren S. E.; Gildersleeve, Ryan Evely ([S.l.] : ROUTLEDGE, 2022)
Transformation of the University imagines preferable futures for the university, building hope for the institution's necessary transformation. It transcends old criticisms and presents fresh ideas on how the institution might be conceived, organised and put into practice while safeguarding that which makes it a university - the pursuit of knowledge. This book is divided into three main parts: Part One - Knowledge' assumes the role of the university in generating knowledge for the benefit of society; Part Two - Cultural Growth' expands on how the university might contribute to and benefit from the cultural growth of society, with both explicit and implicit connections to social and epistemic (in)justice; and Part Three - Institutions' focuses on imaginative processes for enacting the university as an institution that meets the unforeseen future challenges facing societies around the world. With contributions from scholars across the world, Transformation of the University is an essential read for all academics, practitioners, institutional leaders and broad social thinkers who are concerned with the future of the university and its contributions to society.
Keywords: EDUCATION / Philosophy & Social Aspects; Educational change -- South Africa